Author and characters: ancient, narratological, and cognitive views on a tricky relationship - Grethlein, Jonas (Classical philology, 2021)
This article argues that ancient readers had a very different sense of the relation between author and characters from modern literary scholars. The tendency of ancient critics to ascribe to authors utterances of characters bespeaks a distinct understanding of direct speech. This understanding is illuminated through discussions of passages from Plato, Aristotle, and the scholia and then explained in terms of auditory reception and ancient accounts of poetic composition. While at odds with the ontologies of structuralist narratology, the ancient understanding of the author resonates with the recent analysis of imagination in cognitive studies.
Gesehen am 28.06.2022